PENGARUH PERAN KEPALA MADRASAH SEBAGAI LEADER DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA GURU DI MADRASAH ALIYAH SWASTA KOTA PEKALONGAN - Rofi Setyaji; Noor Miyono; Endang Wuryandini (Jurnal Manajemen Pendidikan (JMP), 2022)
Setyaji, Rofi 2021. "The Influence of the Role of the Head as a Leader and Organizational Culture on Teacher Job Satisfaction in the Private MA of Pekalongan City". Thesis. Advisor I Dr. Noor Miyono, M.Si. And Advisor II Dr. Endang Wuryandini, M.Pd.                    The background of this research is teacher dissatisfaction in working at the Private MA of Pekalongan City. The aims of this study were: (1) to determine the effect of the role of the principal as a leader on teacher job satisfaction (2) to determine the effect of organizational culture on teacher job satisfaction (3) to determine the effect of the role of the principal and organizational culture together with job satisfaction. teacher work.                    The population of this study were all teachers of the Private MA of Pekalongan City, totaling 109 people, with a sample of 86 people using proportional random sampling. The data collection method used is the questionnaire method. The data analysis used is descriptive data analysis, prerequisite test and hypothesis testing which includes simple linear regression analysis, as well as multiple linear regression.                    The results of the research are expressed by the equation Y = 21,235 + 0,830 X1 ; correlation strength of 0.821 with a contribution of 0.674 or 67.4%. There is an influence of organizational culture on teacher job satisfaction which is expressed by the equation Y = 18,874 + 0,831X2; correlation strength of 0.837 with a contribution of 0.71 or 70.1%. There is an effect of the role of the principal and organizational culture together on teacher job satisfaction which is expressed by the equation Y = 12.114 + 0.397X1 + 0.498 X2; correlation strength is 0.862 with a contribution of 0.743 or 74.3%. Keywords: the role of the principal as a leader, organizational culture, and teacher job satisfaction.